Effect of brain-based learning with e-comic on vocational students’ motivation and physics learning outcomes - Afida, Nurul Aini; Maryani, Maryani; Nuraini, Lailatul (Universitas Sultan Ageng Tirtayasa, 2025)
The purpose of this study was to examine the effect of brain-based learning accompanied by e-comic media on the motivation and learning outcomes of vocational physics students in understanding energy and its changes. The type of research used was a true experimental study with a posttest-only control design. The research population consists of 10th-grade students at one vocational school in Mojokerto Regency. The measurement tools used in this study are a learning motivation questionnaire and a posttest, which will be statistically analyzed using the Kolmogorov-Smirnov test for normality and the independent samples t-test for hypothesis testing. The validity test results for the learning motivation instrument yielded a correlation coefficient of 0.497 and an r-table value of 0.282. The validity test results indicate that the learning motivation instrument is valid for the study. The normality test results for the learning motivation data and physics learning outcomes between the experimental and control classes showed a significant effect. The results of the T-test for learning outcomes in the experimental class were 0.111 and in the control class were 0.000. Therefore, it can be concluded that H0 is rejected and Ha is accepted, meaning there is a significant effect of the application of the brain-based learning model supported by e-comic media on the motivation and physics learning outcomes of vocational students.